2011
DOI: 10.1143/jjap.50.09nd13
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Motion of Multilayer Film with Alternate Rows of Optical Isomers of Chiral Polymer Film

Abstract: We realized a multilayer film laminated alternately with poly(L-lactic acid) (PLLA) and poly(D-lactic acid) (PDLA) films in order to improve the piezoelectric performance of the PLLA film. In the fabrication processes, the thicknesses of PLLA and PDLA films were reduced to improve the effective electric field, and a multilayer composed of more than 100 layers (PDLA/PLLA multilayer film) was realized to improve the piezoelectric performance. In general, a single PLLA film has a piezoelectric constant of about 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…In order to induce piezoelectricity, the chains must be thermally stretched to transform the a-crystalline form into the b-crystalline form, which represents a change from randomly oriented molecular chains to molecular chains being aligned along the stretched direction. 78,79 It is noted that elongated PLLA lms have no…”
Section: Piezoelectric Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to induce piezoelectricity, the chains must be thermally stretched to transform the a-crystalline form into the b-crystalline form, which represents a change from randomly oriented molecular chains to molecular chains being aligned along the stretched direction. 78,79 It is noted that elongated PLLA lms have no…”
Section: Piezoelectric Materialsmentioning
confidence: 99%
“…PLLA is a transparent and very exible polymeric material, and thus is used for applications in mobile devices as an environmentally friendly, exible, transparent, piezoelectric thin lm. 78,79 Fig. 2 presents PLLA in the a-crystalline form which is thermodynamically stable conformation.…”
Section: Piezoelectric Materialsmentioning
confidence: 99%
“…PLLA is more widely utilized for making piezoelectric devices while PDLA is often used as an agent to improve the piezoelectric and thermo‐mechanical properties of PLLA. [ 35,111–114 ]…”
Section: Piezoelectric Polymersmentioning
confidence: 99%
“…PLLA is more widely utilized for making piezoelectric devices while PDLA is often used as an agent to improve the piezoelectric and thermo-mechanical properties of PLLA. [35,[111][112][113][114] Compared with PVDF, PLLA exhibits a higher shear piezoelectric coefficient value (d 14 ) of ≈12 pm V −1 . [115] Studies have demonstrated that the chirality of the asymmetric carbon atoms in PLLA affects its shear piezoelectric constant.…”
Section: Pla-based Nanofibersmentioning
confidence: 99%
“…[20,21] Therein, the sustainable growth of shear piezoelectric signals gives the PLLA great application potential in the field of actuators and sensors. [21][22][23][24][25] In addition, PLLA is biodegradable and can be decomposed in a hydrolytic or enzymatic condition, [26,27] it is a kind of environmentally friendly biomaterial, which has been applied in flexible electronics and wearable sensors due to excellent biocompatibility. [28][29][30] Currently, greater progress has been made in flexible sensors based on elastic polymers.…”
Section: Introductionmentioning
confidence: 99%